Determining the local low-energy excitations in the Kondo semimetal CeRu4Sn6 using resonant inelastic x-ray scattering - Amorese, Andrea; Haverkort, Maurits W. (Physical review, 2018)
We have investigated the local low-energy excitations in CeRu4Sn6, a material discussed recently in the framework of strongly correlated Weyl semimetals, by means of Ce M5 resonant inelastic x-ray scattering (RIXS). The availability of both 2F52 and 2F72 excitations of the Ce 4f1 configuration in the spectra allows for the determination of the crystal-electric field (CEF) parameters that explain quantitatively the high-temperature anisotropy of the magnetic susceptibility. The absence of an azimuthal dependence in the spectra indicates that all CEF states are close to being rotational symmetric. We show further that the non-negligible impact of the ˇA06 parameter on the ground state of CeRu4Sn6 leads to a reduction of the magnetic moment μc due to multiplet intermixing. This improves the agreement between CEF calculations and the experimentally determined magnetic susceptibility considerably at low temperatures. Deviations that persist at low temperatures for fields within the tetragonal plane are attributed to the Kondo interaction between 4f and conduction electrons. The RIXS results are consistent with inelastic neutron scattering data and are compared to the predictions from ab initio based electronic structure calculations.